MODERN METHODS OF TEACHING ENGLISH IN HIGHER EDUCATIONAL INSTITUTIONS - qizi, Yigitaliyeva Nozimaxon Farxodjon (FAN, TA'LIM VA AMALIYOT INTEGRATSIYASI, 2022)
The material of the article is devoted to the modern methods of teaching foreign languages. The article carries material about the advantages and perspectives of using of described technologies in the process of learning in Higher Educational Institutes. These technologies may be considered as the alternative means of evaluation of students results in their academic activities and personal development.